Endophytic bacterial communities in wild rice (Oryza officinalis) and their plant growth-promoting effects on perennial rice - Tian, Qinglin; Gong, Yurui; Liu, Shuang; Ji, Menglin; Tang, Rui; Kong, Deting; Xue, Zhifeng; Wang, Linglin; Hu, Fengyi; Huang, Liyu; Qin, Shiwen (Frontiers in Plant Science, 2023)
Endophytic bacterial microbiomes of plants contribute to the physiological health of the host and its adaptive evolution and stress tolerance. Wild rice possesses enriched endophytic bacteria diversity, which is a potential resource for sustainable agriculture. Oryza officinalis is a unique perennial wild rice species in China with rich genetic resources. However, endophytic bacterial communities of this species and their plant growth-promoting (PGP) traits remain largely unknown. In this study, endophytic bacteria in the root, stem, and leaf tissues of O. officinalis were characterized using 16S rRNA gene Illumina sequencing. Culturable bacterial endophytes were also isolated from O. officinalis tissues and characterized for their PGP traits. The microbiome analysis showed a more complex structure and powerful function of the endophytic bacterial community in roots compared with those in other tissue compartments. Each compartment had its specific endophytic bacterial biomarkers, including Desulfomonile and Ruminiclostridium for roots; Lactobacillus, Acinetobacter, Cutibacterium and Dechloromonas for stems; and Stenotrophomonas, Chryseobacterium, Achromobacter and Methylobacterium for leaves. A total of 96 endophytic bacterial strains with PGP traits of phosphate solubilization, potassium release, nitrogen fixation, 1-aminocyclopropane-1-carboxylate (ACC) deaminase secretion, and siderophore or indole-3-acetic acid (IAA) production were isolated from O. officinalis. Among them, 11 strains identified as Enterobacter mori, E. ludwigii, E. cloacae, Bacillus amyloliquefaciens, B. siamensis, Pseudomonas rhodesiae and Kosakonia oryzae were selected for inoculation of perennial rice based on their IAA production traits. These strains showed promising PGP effects on perennial rice seedlings. They promoted plants to form a strong root system, stimulate biomass accumulation, and increase chlorophyll content and nitrogen uptake, which could fulfil the ecologically sustainable cultivation model of perennial rice. These results provide insights into the bacterial endosphere of O. officinalis and its application potential in perennial rice. There is the prospect of mining beneficial endophytic bacteria from wild rice species, which could rewild the microbiome of cultivated rice varieties and promote their growth.